The Influence of Religiosity on Consumer Ethical Judgments and Responses Toward Sexual Appeals - Putrevu, Sanjay; Swimberghek, Krist (2013)
This research explores the influence of religiosity on consumer perception of, and response toward, sexual appeals. The first study (survey, national sample; n = 423) examines the relationship between religiosity and consumer response toward sexual appeals using causal modeling. Study 1 finds that high intrinsic religiosity consumers exhibit more adverse ethical judgments toward the company’s use of sexual appeals and these judgments, in turn, result in inferior attitudes and purchase intent toward the advertised brand. To confirm and expand on these findings, the second study (experiment, young adult sample; n = 216) examines the influence of intrinsic religiosity on consumer response toward both sexual and nonsexual appeals. The results show that sexual appeals elicit inferior (superior) ethical judgments, attitudes, and purchase intent among consumers high (low) in intrinsic religiosity. In contrast, nonsexual appeals elicit (un)favorable responses from consumers who are (low) high in intrinsic religiosity.
Keywords: advertising effectiveness; Sexual appeals; Religious influence; ethical judgments